Inteligência computacional aplicada à modelagem e otimização de bioprocessos - Aquino, Pedro Luiz da Mota e (2016)
This work deals with modeling applications, systematic and reliable optimization methodologies of global search, and other computational tools. It is expected that existing computational intelligence methods, encoded in an appropriate tool for the application of process engineering assisted by computer, can lead to useful numerical results for the modeling and optimization of different processes, including biotechnological processes (focus of this work). Thus, different types of methodologies suitable for computer applications, were studied here. The proposed methodologies were implemented and evaluated for the development and optimization of culture media for the fermentation process of Clostridium novyi type B, besides the fermentation process and enzymatic hydrolysis of bagasse associated with the production of bioethanol (1G and 2G). Thus, the potential application of these computational techniques was evaluated to biotechnological systems in different approaches. More specifically, it was performed: Classification of biotechnological systems ( "clustering") in kinetically similar regions to produce cellulosic ethanol (2G ethanol) using fuzzy logic; estimation by global search of kinetic parameters to an alcoholic fermentation model using Simmulated Annealing algorithm (SA) (Contributions to the thematic project FAPESP 2011 / 51902-9); formulation and optimization of economically viable culture media for Clostridium novyi type B using neuro-fuzzy data modeling followed by global search which maximize productivity, also utilizing SA algorithm as a search engine (this step of the project was conducted in partnership with the veterinary pharmaceutical company Vallée SA). The computational tools presented in this work were highly effective for modeling and optimization of the bioprocesses studied.